Judicial review handbook - Fordham, Michael (London, England : Zed Books, 2021)
"...an institution for those who practise public law...it has the authority that comes from being compiled by an author of singular distinction". (Lord Woolf, from the Foreword to the Fifth Edition) The new edition of this Handbook remains an indispensable source of reference and a guide to the case-law in judicial review. Established as an essential part of the library of any practitioner engaged in public law cases, if offers unrivalled coverage of administrative law, including, but not confined to, the work of the Administrative Court and its procedures. Once again completely revised and up-dated, the seventh edition approximates to a restatement of the law of judicial review, organised around 63 legal principles, each supported by a comprehensive presentation of the sources and an unequalled selection of reported case quotations. It also includes essential procedural rules, forms and guidance issued by the Administrative Court. As in the previous edition, both the Civil Procedure Rules and Human Rights Act 1998 feature prominently as major influences on the shaping of the case-law. Attention is also given to impact of the Supreme Court. Here Michael Fordham casts an experienced eye over the Court's work in the area of judicial review, and assesses the signs from a Court that will be one of the key influences in the development of judicial review in the modern era. The author, a leading member of the English public law bar, and now has been involved in many of the leading judicial review cases in recent years and is the founding editor of the Judicial Review journal."--
Summary of Contents JUDICIAL REVIEW HANDBOOK: A DETAILED GUIDE TO THE LAW AND PRACTICE A. THE NATURE OF JUDICIAL REVIEW: keys to understanding what the Court is doing P1 A constitutional guarantee P2 Supervisory jurisdiction P3 Procedural rigour & flexibility P4 Materiality P5 Targets P6 Sources P7 Constitutional fundamentals P8 EU law P9 The HRA P10 Candour & cooperation P11 Precedent & authority P12 Reviewing primary legislation P13 Judicial restraint P14 Critical balance P15 The forbidden method P16 Hard-edged questions P17 Evidence & fact P18 Costs P19 The claim stage P20 Interim relief P21 The permission stage P22 The substantive stage P23 Appeal P24 Remedies P25 Monetary remedies -- B. PARAMETERS OF JUDICIAL REVIEW: further dominant themes shaping the law and practice P26 Delay P27 Public/private law P28 Ouster P29 Interpretation P30 Function P31 Context P32 Modified review P33 Flux P34 Reviewability/non-reviewability P35 Principle of legality P36 Alternative remedy P37 Proportionality method P38 Standing P39 Discretion/duty P40 Inalienability P41 Legitimate expectation P42 Onus P43 Severance P44 Nullity -- C. GROUNDS FOR JUDICIAL REVIEW: public law wrongs justifying the Court's intervention P45 Classifying grounds P46 Ultra vires P47 Jurisdictional error P48 Error of law P49 Error of fact P50 Abdication/fetter P51 Insufficient inquiry P52 Bad faith/improper motive P53 Frustrating the legislative purpose P54 Substantive unfairness P55 Consistency/equal treatment P56 Relevancy/irrelevancy P57 Unreasonableness P58 Proportionality P59 HRA violation P60 Constitutionality P61 Procedural unfairness P62 Consultation P63 Bias P64 Reasons P65 External vitiation
Previous edition: 2012.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Judicial review of administrative acts -- Great Britain; Judicial review of administrative acts -- Great Britain -- Digests; Judicial review -- England; Judicial review -- Wales; Constitutional & administrative law; Electronic books